Real estate web application - Chopra, Rashi (Kansas State University, 2008)
The Real Estate Web Application is an interactive, effective and revenue-generating website designed for the Real Estate Industry. The main objective of this application is to help the Real Estate Company to display unlimited number of property listings on the website. The primary focus is to get familiar to .NET framework and code with ASP.NET and C# .NET to provide a featured GUI which contains sophisticated search engine for buyer's to search for property listings specific to their needs. The search engine not only provides an easy and convenient way to search for listings but also display the entire list of properties in a customized grid format. The buyer can then view the complete specification of each property listing with its features, description and photographs. The application also provides a drag and drop control to save a list of selected property listings while browsing other options on the Real Estate Website. There are hundreds of Real Estate Websites on the World Wide Web but the intention of designing this application is to develop something new, innovative and efficient using latest technologies like AJAX, Java Script, etc which not only enhances the already existing search features available on the internet but also gets rid of their annoying and unessential features. The main emphasis lies in providing a user-friendly search engine for effectively showing the desired results on the GUI.
Keywords: Real Estate; .net; Computer Science (0984)